2021
DOI: 10.1097/tp.0000000000004012
|View full text |Cite
|
Sign up to set email alerts
|

Shotgun Immunoproteomics for Identification of Nonhuman Leukocyte Antigens Associated With Cellular Dysfunction in Heart Transplant Rejection

Abstract: Background. The International Society for Heart and Lung Transplant consensus panel notes that too little data exist regarding the role of non-HLA in allograft rejection. We developed a novel shotgun immunoproteomic approach to determine the identities and potential roles non-HLA play in antibody-mediated rejection (AMR) in heart transplant recipients. Methods. Serum was collected longitudinally from heart transplant recipients experiencing AMR in the absence of donor-specific anti-HLA antibodies (n = 6) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…While also investigating the non-HLA antibody repertoires, Gates et al 135 used immunoproteomics in adult heart transplantation. Sera were collected at different time points from heart transplant recipients with AMR but without donor-specific anti-HLA antibodies and matched controls without rejection.…”
Section: Proteomic Biomarkers In Transplantationmentioning
confidence: 99%
“…While also investigating the non-HLA antibody repertoires, Gates et al 135 used immunoproteomics in adult heart transplantation. Sera were collected at different time points from heart transplant recipients with AMR but without donor-specific anti-HLA antibodies and matched controls without rejection.…”
Section: Proteomic Biomarkers In Transplantationmentioning
confidence: 99%
“…As illustrated by the latter study, genomics and proteomics offer exciting and powerful new approaches to better analyze non-HLA Ab repertoires. In this issue of Transplantation , Gates et al 10 describe a novel, elegant, affinity chromatography approach (shotgun immunoproteomics) for high throughput non-HLA Ag discovery, that they have applied in adult heart transplantation, but which they contend has potential utility in all transplant settings. The authors used this powerful approach to identify, from the sera of patients without DSA, but with or without AMR, Ag targets from individual patient donor heart biopsies obtained at the time of transplantation.…”
mentioning
confidence: 99%
“…Equally significantly, immunofluorescence staining for 4 selected, high prevalence Ag targets in donor endomyocardial biopsies indicated that, as the non-HLA response increased at the time of acute rejection, so did the abundance of the corresponding Ag (junctional plakoglobin, troponin T, prohibitin, and ATP synthase) in graft tissue. Gates et al 10 deduced that the non-HLA Abs examined can inhibit the normal functions of their target Ags and potentially increase their expression in response to loss of function. In chronic AMR, or in patients without AMR, IgG reactivity was more commonly directed against intracellular Ag targets that were likely made accessible by initial graft injury/acute rejection.…”
mentioning
confidence: 99%